مستوى تمكن الطلاب المعلمين بكليات التربية من مهارات اختيار و تطبيق و تطوير طرائق التدريس و علاقة ذلك ببعض المتغيرات - عبدالحميد، عبدالناصر محمد; المليجي، علاء أحمد محمد (جامعة الأزهر - كلية التربية, 2011)
هدفت الدراسة إلى الكشف عن مدى تمكن الطلاب المعلمين بكليات التربية من مهارات اختيار وتطبيق وتطوير طرائق التدريس، وعلاقة ذلك ببعض المتغيرات مثل التخصص الأكاديمي (علمي – أدبي)، المستوى الدراسي (الفرقة الثالثة – الفرقة الرابعة) ونمط الإعداد (تكاملي – تتابعي).\\\\ وتكونت عينة الدراسة من (600) طالبًا وطالبة من ثلاث كليات للتربية هي: كلية التربية بشبين الكوم – جامعة المنوفية، كلية التربية ببنها – جامعة بنها، كلية التربية بتفهنا الأشراف جامعة الأزهر.\\\\ وقد توصلت الدراسة إلى عدة نتائج منها:\\\\ 1- تدني مستوى الطلاب المعلمين بكليات التربية بشكل عام في مهارات اختيار وتطبيق وتطوير طرائق التدريس طبقًا لنتائج تطبيق بطاقة الملاحظة، حيث كانت النسبة المئوية لمجموع درجاتهم (67.2%)، (67.7%)، (63.47%) على الترتيب، وفي المهارات ككل (66.15%)، وجميعها دون مستوى التمكن (80%).\\\\ 2- عدم وجود فروق ذات دلالة إحصائية بين متوسطي درجات الطلاب المعلمين على بطاقة الملاحظة تعزى لمتغير التخصص الأكاديمي (علمي – أدبي).\\\\ 3- وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات الطلاب المعلمين على بطاقة الملاحظة تعزى لمتغير المستوى الدراسي (الفرقة الثالثة – الفرقة الرابعة)، حيث تفوق طلاب الفرقة الرابعة على نظرائهم بالفرقة الثالثة.\\\\ 4- وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات الطلاب المعلمين على بطاقة الملاحظة تعزى لمتغير نمط الإعداد (تكاملي – تتابعي)، حيث تفوق الطلاب في نمط الإعداد التكاملي على نظرائهم في نمط الإعداد ألتتابعي (طلاب الدبلوم العام في التربية). This study aimed to reveal the extent to which student teachers in the skills of selection and application and development of teaching methods, and the relationship with some variables such as academic specialization (scientific - literary). level course (third year - the fourth year) and the pattern of setting (integrated - sequential). The study sample consisted of\\\\\\\ students from\\\\ three colleges of education are: College of Education Shebin EE Kom - University. Egypt. Banha Faculty of Education - University of Banha. Faculty of Education Ptyhna supervision of Al-Azhar University. The study reached several conclusions, including:\\\\ 1-\\\\\\\ low level of student teachers at the elementary education in general in the skills of selection and application and development of teaching methods according to the results of the . (67.2%). (7 .application card. note, where the percentage of the total scores (63. 47%) on.(67.7%). respectively. and the skills as a( 66,15%), all of which are below the level of mastery (80%).\\\\ 2-\\\\\\\ There is no statistically significant differences between the mean scores of student teachers on the note card is due to the variable of academic specialization (scientific - literary).\\\\ 3-\\\\\\\ There are differences between the mean scores of student. statistical significance level (0.05) teachers on the note card due to the variable-level course (third year - the fourth division), where the fourth year students than their counterparts on the third year.\\\\ 4-\\\\\\\ There were statistical differences at the level of (0.051 between the average of the scores of student teachers on the card note due to the variable pattern setting (integrated - sequential). where more than students in the pattern of setting complementary exceed their counterparts in the pattern of sequential setting (Students General Diploma in Education).
Keywords: استراتيجيات التدريس -- الطلاب المعلمون -- طرق التدريس -- المهارات التدريسية -- برامج إعداد المعلمين -- كليات التربية -- جامعة المنوفية -- جامعة بنها -- مصر -- جامعة الأزهر -- الوسائل التعليمية -- التحصيل الدراسي